Changing the policy for intermittent preventive treatment with sulfadoxine–pyrimethamine during pregnancy in Malawi. (December 2017) - Mwendera, Chikondi; Jager, Christiaan; Longwe, Herbert; Phiri, Kamija; Hongoro, Charles; Mutero, Clifford
Abstract Background The growing resistance ofPlasmodium falciparum to sulfadoxine–pyrimethamine (SP) treatment for uncomplicated malaria led to a recommendation by the World Health Organization for the use of artemisinin-based combination therapy. Inevitably, concerns were also raised surrounding the use of SP for intermittent prevention treatment of malaria during pregnancy (IPTp) amidst the lack of alternative drugs. Malawi was the first country to adopt intermittent prevention treatment with SP in 1993, and updated in 2013. This case study examines the policy updating process and the contribution of research and key stakeholders to this process. The findings support the development of a malaria research-to-policy framework in Malawi. Methods Documents and evidence published from 1993 to 2012 were systematically reviewed in addition to key informant interviews. Results The online search identified 170 potential publications, of which eight from Malawi met the inclusion criteria. Two published studies from Malawi were instrumental in the WHO policy recommendation which in turn led to the updating of national policies. The updated policy indicates that more than two SP doses, as informed by research, overcome the challenges of the first policy of two SP doses only because of ineffectiveness byP. falciparu m resistance and the global lack of replacement drugs to SP for IPTp. Conclusion International WHO recommendations facilitated a smooth policy change driven by motivated local leadership with technical and financial support from development partners. Policy development and implementation should include key stakeholders and use local malaria research in a research-to-policy framework.